The Effects of Beta Blockers on Exercise Tolerance and Quality of Life in Congestive Heart Failure Patient - Mrinal Kunj; Divakar Kumar; Anshu Kumar (Journal of Pharmacy and Bioallied Sciences)
Background: Congestive heart failure (CHF) is a serious cardiovascular condition that lowers quality of life (QoL) and impairs exercise tolerance. In terms of morbidity and mortality, beta-blockers, which are often employed in the treatment of CHF, have demonstrated notable advantages. The purpose of this study was to assess how beta-blockers affected the exercise tolerance and QoL of CHF patients. Materials and Methods: In a prospective observational trial, 100 CHF patients between the ages of 40 and 70 were divided into two groups: 50 in the beta-blocker treatment group and 50 in the control group. The 6-minute walk test (6MWT) was used to measure exercise tolerance, and the Minnesota Living with Heart Failure Questionnaire (MLHFQ) was used to measure QoL. Evaluations were conducted both at baseline and 6 months during treatment. Independent t-tests for differences between groups and paired t-tests for comparisons within groups were used in the statistical study. Results: The beta-blocker group’s mean distance traveled during the 6MWT at baseline was 300 ± 50 meters, while the control group was 310 ± 45 meters (P = 0.25). The beta-blocker group improved significantly to 380 ± 40 meters (P < 0.001) after 6 months, whereas the control group only slightly improved (320 ± 48 meters, P = 0.07). The beta-blocker group’s QoL ratings (MLHFQ) increased from a baseline of 45 ± 5 to 30 ± 4 (P < 0.001), but the control group improved somewhat from 44 ± 6 to 42 ± 5 (P = 0.2). After 6 months, both outcomes showed statistically significant differences between groups (P < 0.01). Conclusion: Beta-blocker therapy significantly improves exercise tolerance and QoL in CHF patients over a 6-month period. These findings support the integration of beta-blockers as a cornerstone of CHF management.